(untitled) (Bangladesh Journal of Agricultural Research, 2014)
Combining ability was studied for kernel yield and yield components in a 8×8 diallel cross of waterlogged tolerant maize. Significant general and specific combining ability variances were observed for all the characters studied. Additive genetic variance was preponderant in plant height, ear height, ear length, ear diameter, and kernel weight and non-additive gene action was involved in days to silking, number of kernels per ear and kernel yield. The parental lines E-31 and E-79 were found to be the best general combiners for yield. The good combining parents for different traits could be used in hybridization to improve yield and other desirable traits as donor parents for the accumulation of favourable genes. The cross combinations, E 31× E 40, E 31× E 64, E 31× E 79, E 38× E 40, E 58× E 79, E 63× E 79, E 64 × E 79 showing significant and positive sca effects can be used for commercial hybrid variety development after verifying them at different locations. DOI: http://dx.doi.org/10.3329/bjar.v39i2.20430 Bangladesh J. Agril. Res. 39(2): 283-291, June 2014